Molière et le théâtre arabe Réception moliéresque et identités nationales arabes - Langone, Angela Daiana (De Gruyter, 2016)
Molière, often considered the 'godfather of Arab theatre', was first introduced to the Arab world in 1847 by Marun Naqqaš and his adaptation of The Miser. Since then, Molière has never ceased to influence Arab dramaturgy. Discussing a series of plays by authors from Lebanon, Egypt, Tunisia and Morocco, this study aims at defining Molière's role in the development of a national Arab theatre.